Numerical modelling investigation of rock mass behaviour under gravity dams - Alshkane, Younis Mustafa Ali (2015)
The study of rock mass behaviour is a broad subject in the rock mechanics field which still needs more research and investigation, especially for geotechnical issues associated with dam construction. Since it is difficult to study rock mass behaviour at a large scale in the laboratory, the numerical modelling technique is an alternative method which can be used efficiently in this field. In this thesis two codes have been selected for this purpose. The first code was a continuum code FLAC (Fast Lagrangian Analysis of Continua), which was used to study the effect of a weak rock joint on the stability of a concrete gravity dam as well as to model the gravity dam with its foundation as a continuum. The second code was the Distinct Element Method (DEM) software package UDEC (Universal Distinct Element Code), which was used to study the fully jointed rock mass behaviour under the gravity dam. The equivalent strength and deformability parameters of jointed rock masses were also studied using UDEC. Furthermore, the cause of strain hardening behaviour in jointed rock samples was studied using UDEC and experimental methods.